Mechanism of ferroptosis in traditional chinese medicine for clinical treatment: A review - Liu, Jiajiao; Jiang, Guanyin; He, Pengfei; Du, Xing; Hu, Zhenming; Li, Fuxiang (Frontiers in Pharmacology, 2023)
Ferroptosis is an iron-dependent regulation of cell death driven by lipid peroxidation, which is intracellularly dependent on iron and independent of other metals, and morphologically, biochemically, and genetically distinct from apoptosis, necrosis, and autophagy. Ferroptosis is closely related to physiological and pathological processes, such as development, aging, and immunity, and it plays an important role in a variety of diseases. In many departments, traditional Chinese medicine plays an increasingly important role in their clinical treatment. In recent years, an increasing number of studies have been conducted on the mechanism of ferroptosis in traditional Chinese medicine. However, the role of ferroptosis in the clinical treatment of traditional Chinese medicine requires further exploration. This article mainly introduces the application of ferroptosis in studies of the mechanism of traditional Chinese medicine to help clinicians understand the current status of traditional Chinese medicine therapy for the treatment of ferroptosis-related diseases.